PENGARUH MUSIK INSTRUMENTAL TERHADAP KETERAMPILAN MEMBACA PUISI PADA SISWA - Nabila Shafna; Masnunah; Endang Surtiyoni (Jurnal Bastra (Bahasa dan Sastra), 2024)
This research aims to determine whether there is an influence or not The Use of Instrumental Music on Poetry Reading Skills in Class III students at SDN 232 Palembang. The research method used is experimental method. The research samples taken in this research were class III.B consists of 22 students as the experimental class and class III.C consists of 22 students as a control class. Sampling technique in research This is a purposive sample. Data collection uses tests so that it can be done knowing students' reading skills and documentation to analyze documents in writing. The data analysis technique used is test analysis Paired Sample T-test. The results of the research carried out showed that the final result the experimental class value was an average value of 88.18, while the control class obtained an average score of 49.55. Based on data analysis and discussion In this research, it can be concluded that: There is an influence of use Instrumental Music on Poetry Reading Skills in Class III Students SDN 232 Palembang.